Emotive validity and the eye in the hand – Representing visual reality with digital technology. (June 2021) - Boeriis, Morten
Highlights: Visual validity in manipulated reality of vernacular digital photography. Emotive coding orientation as photographic fidelity to feelings. Photographetic empathy as reverberation through digital sensorimotor imitation. Abstract: Smartphone photography and social media are central in our everyday social lives, and they have paved the way for extremely fast distribution and sharing of our digital photographic texts. The new technology has profound consequences for the pace at which conventionalisation of new social practices can take place, and, consequently, at this point in history our understanding of visual manipulation is undergoing radical changes. This article explores the social semiotic concept visual validity presented by Kress and van Leeuwen in the 3 rd edition of their influential book Reading Images, the grammar of visual design (2020) and discusses in what ways this concept is a fertile new approach to comprehending and analysing the contemporary digitally manipulated reality of vernacular photography. The engagement with the social semiotic theory is anchored in the author's own experiences as a practising photographer and observations of students' practical and theoretical work with photography. It is argued in the article that a new category of represented visual reality, emotive coding orientation, needs to be added to the social semiotic theory to encompass the perspective that photographs may not convey a naturalistic fidelity to how a depicted situation 'really looked' at the time it was photographed, but rather convey an emotional fidelity to how the depicted situation 'really felt' to the photographer. The article proceeds to pursue how we share photographic images as bodily experiences with the camera as an extension of our sensory motor apparatus, and consequently a part of our distributed cognitive system and of our social environment. The concept photographetic empathy (derived from Abercrombie's (1964) notion 'phonetic empathy') is introduced to elucidate how the smartphone camera enhances a sensibility to a (more) bodily experience of photography caused by empathetic reverberation through digital sensorimotor imitation.